Optimization of Coaching and Counseling by Bhabinkamtibmas to Prevent Crimes Committed by Recidivists at Polres Kudus - Munawar, Muhammad Haidar Yaafi (Advances in Police Science Research Journal, 2024)
This study aims to optimize the coaching and counseling, referred to as Binluh, conducted by Bhabinkamtibmas to prevent crimes committed by recidivists. The method used is qualitative, with the research object being Bhabinkamtibmas in the jurisdiction of Polres Kudus. The research findings indicate that Binluh conducted by Bhabinkamtibmas for recidivists is not yet optimal in terms of Organizational Resource (SDO), specifically in Human Resources (man), budget (money), facilities and infrastructure (materials), and Methods (methods). Additionally, Binluh conducted by Bhabinkamtibmas for recidivists is also not optimal in the aspect of System and Method (Sismet), which includes planning, organizing, actuating, and controlling. To address the problem of the suboptimal Binluh by Bhabinkamtibmas, optimization in the aspect of quality through increasing competence (knowledge, skills, and attitude) is necessary. This includes optimizing education, training, technical guidance, knowledge enhancement, instructions and direction, motivation, and rewards for Bhabinkamtibmas. In terms of quantity, special and clear assignments should be made to avoid overlapping tasks. To improve the System and Method (Sismet) of Binluh by Bhabinkamtibmas, planning should incorporate Binluh for recidivists into the activity plans and specific agendas of Bhabinkamtibmas. With optimal planning, the organization and execution of Binluh activities will be more effective as they are carried out in a well-organized manner. The Binluh activities for recidivists by Bhabinkamtibmas can be further optimized by strengthening control through supervision, assistance, reporting, analysis, and evaluation (Anev). By optimizing the SDO and Sismet aspects, Binluh activities will align with the systems, management, and operational success standards set by the Police institution, specifically regarding the implementation of Binluh by Bhabinkamtibmas in preventing crimes committed by recidivists in Polres Kudus.